Treatment with Simvastatin and Low-dose Aspirin Depresses Thrombin Generation in Patients with Coronary Heart Disease and Borderline-high Cholesterol Levels - Musiał, Jacek; Undas, Anetta; Undas, Robert; Brożek, Jan; Szczeklik, Andrzej (Thrombosis and Haemostasis, 2001)
Aspirin and statins are beneficial in coronary heart disease across a broad range of cholesterol levels. We assessed the effects of low-dose aspirin (75 mg daily) on thrombin generation in patients with coronary heart disease and average blood cholesterol levels. We also investigated whether in patients with borderline-high cholesterol level who have been already taking aspirin, additional treatment with simvastatin would affect thrombin generation.Seven-day treatment with low-dose aspirin decreased thrombin generation ex vivo only in patients with total cholesterol 5.2 mmol/L. In patients with higher cholesterol levels aspirin had no effect. In these patients, already taking low-dose aspirin, additional three-month simvastatin treatment resulted in a reduction of thrombin generation. This demonstrates that low-dose aspirin depresses thrombin generation only in subjects with desirable blood cholesterol levels, while in others, with borderline-high cholesterol, thrombin formation is being reduced following the addition of simvastatin.
Keywords: Aspirin; simvastatin; thrombin generation